Crystalline and pseudo-crystalline phases of polyacrylonitrile from molecular dynamics: Implications for carbon fiber precursors. (24th October 2018) - Shen, Tongtong; Li, Chunyu; Haley, Benjamin; Desai, Saaketh; Strachan, Alejandro
Abstract: The molecular structure of spun polyacrylonitrile (PAN) fibers used in the production of carbon fibers (CFs) is known to critically affect the microstructure and, consequently, the properties of the final fiber. We use molecular dynamics (MD) simulations to predict the molecular structure of the crystalline regions of spun PAN. We characterized how tacticity and the arrangement of torsional angles along the backbone affect packing of the chains and lattice parameters. Most configurations, regardless of tacticity, loose periodicity along the chain axis during relaxation resulting in pseudo-crystalline structures. Simulated X-ray diffraction (XRD) patterns of these pseudo-crystalline structures show excellent agreement with recent experimental measurements and reveal that intermolecular spacing decreases as backbone trans/gauche ratio increases corresponding to different experimental conditions. Stability and stiffness also increase as backbone trans/gauche ratio increases. A syndiotactic system with planar zig-zag configuration results in crystalline order along the c axis; this more ordered structure has the lowest potential energy and highest stiffness of all structures studied. The predicted XRD pattern differs significantly from those of the pseudo-crystalline structures but, interestingly, it matches the multi-peak fingerprint reported experimentally in solution-grown single crystals of PAN. The simulations shed light into long-standing discrepancies in XRD patters of PAN precursors. Graphical abstract: Highlights: Characterize the effects of tacticity and torsion angles on PAN chain packing. Simulated XRD patterns of pseudo-crystalline structures show excellent agreement with experiments. A syndiotactic system with planar zig-zag configuration shows the lowest potential energy and highest stiffness.